The United States and Cambodia, 1870-1969 : from curiosity to confrontation - Clymer, Kenton J. (RoutledgeCurzon studies in the modern history of Asia, 2004)
Spanning from the first US contacts with Cambodia in the nineteenth century up until the late 1960s and the outbreak of war with Vietnam, this book is the first to systematically explore American relations with Cambodia.